Clinicophysiological effects of electroacupuncture for anaesthesia of neck and thorax in dogs - KUMAR, GULSHAN; KUMAR, AMRESH (The Indian Journal of Animal Sciences, 2014)
Electrostimulation with a current of 3-5 volts in adjustable wave form at a frequency of 130-150 Hz of acupoints GV20, LU-1, LIV-14, TW-8, CV-4 (group 1); GV-20, LU-I, LIV-14, TW-8, CV-4 and LI-14 (group 2) and GV-20 and auricular analgesia acupoints bilaterally (group 3) in dogs produced excellent anaesthesia of dorsal part of neck in animals of group I, good anaesthesia of dorsal, ventral and lateral aspect of neck and ventral aspect of thorax in group 2 and excellent analgesia of ventral thorax and good analgesia of neck with no desensitization of thorax in animals of group 3. The analgesia lasted as long as stimulation continued. The cardiopulmonary effects were transient and compensated in 30-40 min after electroacupuncture with no significant effect on tidal volume, central venous pressure and electrocardiogram up to 60 min after electroacupuncture.